The housing debate - Lowe, Stuart, 1950- (Book collections on Project MUSE., 2011)
The emergence of Britain as a home-owning society has implications for how people think about housing. Housing is used: as a pension fund; to give resources for care needs; and to sponsor access to private education. This text argues that housing is at the forefront of public policy and as a pillar of post-industrial welfare state.